An anthropogenic factor contributing to the forest land use changes and its socio-economic impact on the Temiar community in Lojing, Kelantan, Malaysia - Baharom, Nor Azmi; Zaki, Pakhriazad Hassan; Ismail, Mohd Hasmadi; Bawon, Paiman (AESS Publications, 2024)
This study investigates human-induced factors influencing changes in forest land use and assesses the socio-economic impacts of the Temiar community in Lojing Highland. The assessment investigates perceptions of forest change, scrutinizing both negative impacts and positive aspects. A cross-sectional household survey involving 550 households, coupled with questionnaires and field observations, utilized descriptive and correlation analysis. Findings reveal that deforestation is influenced by accessibility, land use, government policies, human activities, ecological factors, and population dynamics. While highlighting severe threats to biodiversity, respondents also perceive Land Use and Land Cover Change (LULC) as an emerging economic opportunity, recognizing its role in income generation and job creation. Infrastructure developments have remarkably improved the overall quality of life, especially job prospects. These new opportunities reduce reliance on forest sales, promoting economic diversity. Results highlight the threats of human-induced change while emphasizing the potential for economic growth and improved living standards for the Temiar community. In order to ensure the continuity of common life, there is a need for an improved focus on implementing sustainable practices that balance conservation and economic advancement in the Lojing Highland.